(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2017)
The article presents the antecedents and foundations which led to the construction of the website Science in the Community, a virtual environment just created to share experiences on local cultural knowledge using the internet. Initially, it describes the proposal of folk knowledge insertion into chemistry and science education in Brazil and other related emphases in the international literature, highlighting teachers’ education, its problems and a debate involving indigenous knowledge and the nature of science. Next, it describes the results of empirical inquiries in classrooms and the convergence with literature to offer epistemological content for teachers based on hybrid narratives. As a theoretical background, it presents the concepts of hybridization/hybridism, of narrative and the epistemological dimension of the analysis carried out. The methodological procedures emphasize the construction of hybrid utterances and their dialogic, semantic, syntactic and iterative architecture; the development of activities on languages, images, assertions from literature, and the way the epistemological content was analyzed and organized according to five axes/texts: the knowledges and their contexts, languages, practices, theories, and representations. This set of resources is for those who want to deepen their knowledge on local and scientific knowledge relationships, underlining the mixing of languages as a way to communicate both contents, the absence of authoritarian voice on such a construction and the inextricable link between knowledge and context for the task of knowledge’s representation and epistemological comparison.